Revisiting Aspect in Mild Cognitive Impairment and Alzheimer's Disease: Evidence From Greek - Manouilidou, Christina; Roumpea, Georgia; Nousia, Anastasia; Stavrakaki, Stavroula; Nasios, Grigorios (Frontiers in Communication, 2020)
The study investigates the ability of Greek-speaking individuals diagnosed with mild Alzheimer’s Disease (mAD) and Mild Cognitive Impairment (MCI) to produce verbs that vary with respect to their grammatical and lexical aspect. While grammatical aspect has been examined in aphasia, there are only a few studies dealing with this in neurodegenerative conditions and their findings are contradictory. We further investigate aspect by examining not only grammatical but lexical aspect as well and how their semantic and temporal features affect mAD and MCI individuals’ performance. Thus, the major innovation of the study is that it examines aspect not only as a functional feature but also as a lexical variable, something addressed for the first time. We also investigate whether grammatical aspect interacts with lexical aspect and with time reference. Finally, by looking at Greek, we further contribute to cross-linguistic perspective of aspect investigation. 11 MCI and 11 mAD individuals participated in a picture naming task, targeting the investigation of lexical aspect, and a sentence completion task, targeting the investigation of grammatical aspect and its interaction with lexical aspect and time reference. Both groups were found to be impaired in both tasks when compared to healthy controls. In the naming task, both group and lexical aspect were significant predictors for participants’ performance. Specifically, more impaired performance was found in states (believe), achievements (break) and semelfactives (hit) compared to activities (run) and accomplishments (build) for both groups. In the sentence completion task, apart from group, neither grammatical or lexical aspect nor tense were significant predictors for participants’ performance. While results indicate that both grammatical and lexical aspect are impaired in AD and MCI, a closer look suggests a dissociation regarding the temporal feature of duration. Specifically, as grammatical feature, duration does not appear to affect participants' choice between perfective and imperfective aspect. As a lexical variable, on the other hand, and as part of the lexical representation of a verb, duration (together with internal structure) appears to play a role in verb naming. Finally, the lack of interaction between lexical and grammatical aspect also indicates that these two subsystems can be affected differentially.